Cystic Bone Lesions in Horses and Humans: A Comparative Review - von Rechenberg, Brigitte; McIlwraith, C. W.; Auer, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Cases of cystic bone lesions in horses and humans were reviewed in the literature. These lesions are radiolucent areas of bone, recognized as subchondral cystic lesions in the horse (SCL), intra-osseous ganglia (IOG), subchondral bone cysts secondary to osteoarthrosis (OAC), and unicameral bone cysts (UCB) in humans. Their morphology is quite similar, consisting of lesions with a distinct cyst wall, and a cavity filled with fibrous tissue and yellowish mucoid fluid. The lesions are surrounded by sclerotic bone and can be easily diagnosed radiographically. SCL, IOG and OAC occur in the subchondral bone close to the adjacent joint, whereas UCB occur in the metaphysis of long bones. Their aetiology and pathogenesis is still unknown, although primary damage to the subchondral bone, cartilage or local blood supply and growth disturbances are discussed. In this review 703 lesions of SCL in horses, 289 lesions of IOG and 1460 lesions of UCB in humans were compared in their anatomical location and clinical signs. SCL and OAC resembled each other with respect to anatomical location. A correlation of affected bones could not be found for all four groups. Clinical presentation concerning age was most similar for SCL and UCB with both lesions mainly occurring in young individuals. Gender predominance of males was present in SCL, IOG and UCB. Clinical diagnosis was either incidental, or connected with intermittent pain in all lesions except for OAC. Additionally, the lesions were also found in conjunction with degenerative joint disease (SCL, OAC) or pathological fractures (UCB). Cystic bone lesions were either treated conservatively, surgically with curettage alone, curettage in combination with grafting procedures, or intra-lesional application of corticosteroids. SCL and UCB were similar in their biological behaviour concerning their slow response to the therapy and relatively high recurrence rate. None of the cystic bone lesions were comparable, and a common aetiology and pathogenesis could not be found.In a literature review cases of cystic bone lesions in horses and humans were compared with the goal to find a common aetiology and pathogenesis. Cystic bone lesions occur in horses as subchondral cystic lesions (SCL), and in humans as either intra-osseous ganglia (IOG), subchondral cystic lesions secondary to osteoarthrosis (OAC) or unicameral bone cysts (UCB). IOG and OAC compare with SCL mainly in the anatomical location. IOG and SCL resemble each other in size, clinical signs and histology, whereas UCB and SCL show a similar biological behaviour regarding their therapeutic response and recurrence rate. None of the cystic bone lesions in humans were comparable to the SCL in horses in all aspects. A common aetiology and pathogenesis could not be established.
Keywords: Cystic bone lesions; subchondral cystic lesions; intra-osseous ganglion; subchondral cystic lesions secondary to osteoarthrosis; unicameral bone cysts